HERPES SIMPLEX VIRUS (HSV) KERATITIS BILATERAL WITH FILAMENTOUS - Karniela Ayuni Putri; Havriza Vitresia (HUMAN CARE JOURNAL, 2021)
Introduction: Herpetic keratitis is caused by herpes simplex virus and is a common cause of corneal blindness. Generally herpes simplex keratitis is a unilateral disease, but bilateral disease has been reported in 1,3 % to 10,9 % of patients. Filamentous keratitis most often caused by dry eye, especially aqueous tear-deficient dry eye. Objective: To report a case of bilateral herpes simplex virus keratitis bilateral with filamentous. Method: A 45 years old man was admitted to Dr. M. Djamil Hospital Padang presented with glare and blurred on both eyes since 1 week ago. VA RE is 6/30, VA LE is 6/60. On ophthalmology examination were conjunctival and ciliary injection. On the cornea of both of eyes, found infiltrate numular shaped almost all of layer of the cornea. Cornea sensitivity was decreased on both eyes. Patient diagnosed by numularis keratitis of both eyes and therapy is oral and topical acyclovir. After 2 weeks therapy, we found filamentous on left eye. Debridement of filament was performed and the therapy was continued. Result: There are improvement of visual acuity and clinical feature. VA RE 6/15, LE 6/40. Subjectively, patient feel comfort. The sign of glare and photophobia are decrease. Density of infiltrate was decrease and no filamentous was found.